The criminalization of black children: race, gender, and delinquency in Chicago's juvenile justice system, 1899-1945 - Agyepong, Tera Eva (Justice, power, and politics, 2018)
"In this book, Tera Agyepong explores the vital role children played in the construction of ideas of criminality in early twentieth century Chicago. For African American children, youthfulness--far from being a marker of purity or innocence--was a factor in subjecting them to particular institutional, social, and economic vulnerabilities at the hands of the juvenile justice system. At a moment when blackness was becoming a marker of criminality, their race overrode the potential protections their status as children could have provided them"--